The Influence of Service Quality on Customer Satisfaction at the Dedi Motor Workshop in Bawan, Ampek Nagari District: Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Bengkel Dedi Motor di Bawan Kecamatan Ampek Nagari - Mulyadi (International Journal of Management and Business (IJMB), 2024)
The development of the business developments have evolved from being just an ordinary business to becoming a global business. The company provides various variations in terms of attractive services to customers, the services provided to customers are vehicle repair services providing new services to retain customers. Dedi Motor Bawan Workshop, Ampek Nagari District must be able to provide quality service facilities compared to competitors, so that service innovation occurs which is needed, one of which is is by utilizing information system technology which every customer's wishes are recorded in the information system. Then, using a questionnaire distributed to 100 respondents, the data was collected and analyzed using SPSS. The results obtained are that service quality has a significant effect on customer satisfaction which is revealed using the F test results where the f table value of 1.98 is smaller than the t value of 175.2636 and the significance value is smaller than 0.005. This causes Ho to be rejected and Ha to be accepted.